RELN gene-related drug-resistant epilepsy with periventricular nodular heterotopia treated with radiofrequency thermocoagulation: a case report - Li, Zijian; Wang, Fuli; He, Zhidong; Guo, Qi; Zhang, Jinnan; Liu, Songyan (Frontiers in Neurology, 2024)
An increasing number of gene mutations associated with epilepsy have been identified, some linked to gray matter heterotopia—a common cause of drug-resistant epilepsy. Current research suggests that gene mutation-associated epilepsy should not be considered a contraindication for surgery in epilepsy patients. At present, stereoelectroencephalography-guided radiofrequency thermocoagulation is an important method to treat periventricular nodular heterotopia-associated drug-resistant epilepsy. We present a case of drug-resistant epilepsy, accompanied by periventricular nodular heterotopia and a heterozygous mutation of the RELN gene, successfully treated with radiofrequency thermocoagulation, resulting in a favorable outcome.